2019
DOI: 10.1002/chem.201904255
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Library of Thiophene‐Based Drug‐Like Lego Molecules: Evaluation of Their Anion Binding, Transport Properties, and Cytotoxicity

Abstract: The anion-bindinga nd transport properties of an extensive library of thiophene-based molecules are reported. Seventeen bis-urea positional isomers, with different binding conformationsa nd lipophilicities, have been synthesized by appending a-o rb-thiopheneo ra-, b-, or g-benzo[b]thiophene moieties to an ortho-phenylenediamine central core, yielding six subsets of positional isomers. Through 1 HNMR, X-ray crystallography, molecular modelling,a nd anion efflux studies, it is demonstrated that the most active t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…The 1 H NMR binding studies (vide supra) showed that the α-, βand γ-benzo[b]thiophene (thio)urea motifs recognize chloride thorough the binding modes presented in Scheme 3, in agreement with the experimental and theoretical findings previously observed for chloride complexes of benzo[b]thiophene-based bis-ureas. [6] Therefore, the geometry of the chloride complexes 1-24 were computed for a single binding scenario, with the receptors adopting the putative binding conformations sketched in Scheme 1 and Scheme 2.…”
Section: Theoretical Insights Into Chloride Binding Affinitymentioning
confidence: 99%
See 3 more Smart Citations
“…The 1 H NMR binding studies (vide supra) showed that the α-, βand γ-benzo[b]thiophene (thio)urea motifs recognize chloride thorough the binding modes presented in Scheme 3, in agreement with the experimental and theoretical findings previously observed for chloride complexes of benzo[b]thiophene-based bis-ureas. [6] Therefore, the geometry of the chloride complexes 1-24 were computed for a single binding scenario, with the receptors adopting the putative binding conformations sketched in Scheme 1 and Scheme 2.…”
Section: Theoretical Insights Into Chloride Binding Affinitymentioning
confidence: 99%
“…À S δÀ bond, in agreement with the V s distribution of the isolated benzo[b]thiophene. [6] Of note, the The twisting of benzo[b]thiophene binding motifs was measured using the torsion angle ξ at the C α /C β /C γ À N central bond between the urea binding unit and the heteroaromatic fragment, as defined in Scheme 3. The values obtained for the twenty-four optimized geometries (see Table S1) were also cluster analyzed and are listed in Table 2.…”
Section: Theoretical Insights Into Chloride Binding Affinitymentioning
confidence: 99%
See 2 more Smart Citations
“…Félix and colleagues reported thiophene appended transporters ( 41 – 43 ) on an ortho ‐phenylenediamine central core which bind with anions by urea and C−H binding groups in a cooperative fashion (Figure 12 B–C). [46] The fluorinated analogues were found to be more active towards anions over non‐fluorinated derivatives and display cytotoxicity against tumour cell lines such as HeLa, MCF‐7 and A549. Recently Manna and co‐workers described conformationally controlled bis(thiourea) derivatives ( 44 a – 44 f ) based on 1,2‐diphenylethylenediamin scaffold.…”
Section: Anionophores and Their Biological Studiesmentioning
confidence: 99%